Impact of COVID‐19 on initial emergency medical services certification in the United States - Jonathan R. Powell; Jennifer Cotto; Jordan D. Kurth; Rebecca E. Cash; Mihaiela R. Gugiu; Ashish R. Panchal (Journal of the American College of Emergency Physicians Open)
Abstract Objective As the COVID‐19 pandemic began, there were significant concerns for the strength and stability of the emergency medical services (EMS) workforce. These concerns were heightened with the closure of examination centers and the cessation of certification examinations. The impact of this interruption on the EMS workforce is unclear. Our objective was to evaluate the impact of COVID‐19 on initial EMS certification in the United States. In addition, we evaluated mitigation measures taken to address these interruptions. Methods This study was a cross‐sectional evaluation of the National Certification Cognitive Examination administration and results for emergency medical technician (EMT) and paramedic candidates. We compared the number of examinations administered and first‐attempt pass rates in 2020 (pandemic) to 2019 (control). Descriptive statistics and 2 one‐sided tests of equivalence were used to assess if there was a relevant difference of ±5 percentage points. Results Total number of examinations administered decreased by 15% (EMT, 14%; paramedic, 7%). Without the addition of EMT remote proctoring, the EMT reduction would have been 35%. First‐time pass rates were similar in both EMT (−0.9%) and paramedic (−1.9%) candidates, which did not meet our threshold of a relevant difference. Conclusion COVID‐19 has had a measurable impact on examination administration for both levels of certification. First‐time pass rates remained unaffected. EMT remote proctoring mitigated some of the impact of COVID‐19 on examination administration, although a comparison with mitigation was not assessed. These reductions indicate a potential decrease in the newly certified workforce, but future evaluations will be necessary to assess the presence and magnitude of this impact.